2018
DOI: 10.1071/rdv30n1ab128
|View full text |Cite
|
Sign up to set email alerts
|

128 Evidence that Pregnancy-Associated Serum Protein A (PAPP-A) Plays Role on Bovine In Vitro Embryo Production

Abstract: The aim of present work was to assess the effects of pregnancy-associated serum protein A (PAPP-A) during oocyte in vitro maturation (IVM) on meiosis progression, DNA fragmentation, IGF-1 free bioavailability, as well as effects on embryo yield and transcriptional profile of matured cumulus–oocyte complexes (COC). First, the COC from a local abattoir were submitted to IVM for 24 h with TCM-199 serum-free medium supplemented with PAPP-A (100 ng mL−1: P100 group) or not (control group). The matured oocytes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…We found that rbIGFBP-4 neither affected the percentage of MII-stage oocytes nor cumulus expansion 22–24 h post IVM and did also not affect embryo production until 192 hpi. Similar results were found by Giroto et al (2018) [ 43 ], as they added IGFBP-4 proteolytic enzyme PAPP-A during the COCs IVM, suggesting that the autocrine and paracrine effect of IGFs produced by COCs during IVM did not affect the capacity of the oocytes for blastocyst formation. Moreover, Nicholas et al (2005) [ 44 ] did not find any differences in the cleavage rate of IVM oocytes derived from follicles with different IGFBP-4 profiles.…”
Section: Discussionsupporting
confidence: 87%
“…We found that rbIGFBP-4 neither affected the percentage of MII-stage oocytes nor cumulus expansion 22–24 h post IVM and did also not affect embryo production until 192 hpi. Similar results were found by Giroto et al (2018) [ 43 ], as they added IGFBP-4 proteolytic enzyme PAPP-A during the COCs IVM, suggesting that the autocrine and paracrine effect of IGFs produced by COCs during IVM did not affect the capacity of the oocytes for blastocyst formation. Moreover, Nicholas et al (2005) [ 44 ] did not find any differences in the cleavage rate of IVM oocytes derived from follicles with different IGFBP-4 profiles.…”
Section: Discussionsupporting
confidence: 87%